Microwave-assisted synthesis, electrochemistry and spectroelectrochemistry of amphiphilic phthalocyanines - KOCA, ATIF (ELSEVIER SCIENCE SA, 2015)
Novel hexadeca-substituted metallophthalocyanines (M = Cu, Ni, In) carrying eight hexyloxy groups on non-peripheral positions together with four chloro and four p-sulphonylphenoxy groups on peripheral positions have been synthesized by using microwave irradiation. All newly synthesized amphiphilic phthalocyanine complexes have been characterized by using elemental analysis, Fourier transform infrared spectroscopy, proton nuclear magnetic resonance, mass and UV-vis spectroscopy techniques. The electrochemical behavior of the phthalocyanines was investigated by cyclic voltammetry and square wave voltammetry on a platinum-working electrode. While all complexes gave common phthalocyanine ring-based electron transfer processes, changing the metal center especially affected the aggregation and chemical stabilities of the complexes during the redox reactions. Aggregation tendency of copper phthalocyanine was also studied in methanol and no aggregation was observed in the concentration range from 2 x 10(-6) to 12 x 10(-6) mol dm(-3). (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Metallophthalocyanines; Hexadeca-substitution; Amphiphilic; Microwave irradiation; Electrochemistry; Spectroelectrochemistry; METAL-FREE PHTHALOCYANINES; POLYMERIC PHTHALOCYANINES; COPPER; COBALT; DERIVATIVES; ABSORPTION; SEPARATION; COMPLEXES; BEARING